Cutaneous abscess caused by Corynebacterium lactis in a companion dog - Azevedo de Paula Antunes, Joao Marcelo; Ribeiro, Marcio Garcia [UNESP]; Demoner, Larissa de Castro; Ramos, Juliana Nunes; Pereira Baio, Paulo Victor; Simpson-Louredo, Liliane; Santos, Cintia Silva; Hirata, Raphael; Ferioli, Raquel Beneton; Cruz Romera, Adriana Resmond; Vieira, Veronica Viana; Mattos-Guaraldi, Ana Luiza (Elsevier B.V., 2015)
Many new, emerging and re-emerging diseases of humans are caused by pathogens which originate from animals or products of animal origin. Cotynebacterium lactis, a recently described species of the genus anynebacterium, was first isolated from milk of asymptomatic cows. In the present study a cutaneous abscess caused by C. lactis in a dog was recognized by cytologic and histologic examination in addition to 16S rRNA gene analysis of the microorganism. Therefore, C lactis should be included among other bacterial species recognized as emerging pathogens for companion animals. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Corynebacterium lactis; Dog infection; Cutaneous abscess